Sistemas de Informação nas Organizações Empresariais (estudo de caso) - Azevedo, Liduina Ribeiro (2006)
It describes the Systems of Information for the enterprise organizations giving to emphasis for the information telling its concepts and its definitions. The information is the part key for any taking of decision, therefore the necessity of the same one well to be worked and to be selected by the Systems of Information. A System of Information characterizes for a series of elements or interrelated components that they collect (entered), they manipulate and they store (process), spreads (exit) the data and information and the taking of decision in an organization, them assists controlling and employees to analyze problems, to visualize solutions and to create new products. One is about a specialized type of system, being able to be defined as a set of interrelated components working together to collect, to recoup, to process, to store and to distribute the information with the purpose to facilitate the planning, the control, the coordination, the analysis and the power to decide process in companies and organizations. The present study the advantages had as objective to analyze the System of information of the Mercadinhos São Luiz being shown its deficiencies but also to work with systems of structuralized information capable to answer to the expectations of the collaborators and to take care of all to the necessities of the company.